2017
DOI: 10.1037/pha0000118
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate reduces basal anxiety and relieves ethanol withdrawal-induced anxious behaviors in male rats.

Abstract: Anxiety disorders are associated with increased impairments in psychosocial functioning, work productivity and health-related quality of life. In addition, anxiety is a common symptom of ethanol withdrawal and it strongly contributes to relapse. Benzodiazepines are frequently prescribed for relief of anxiety and ethanol withdrawal symptoms but considerable side effects, such sedation, tolerance and dependence, are observed during treatment. Therefore, better drugs are needed for the treatment of anxiety states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…17 The dose range of topiramate reported in previous experimental studies is broad and often depends on the method of administration. For example, the efficacy of topiramate at a dose of 40-160 mg/kg/day in an inflammatory hyperalgesia model in rats 18 was demonstrated, and at a dose of 40 mg/kg/day 19 in studies on behavioral symptoms in rats. It has also been reported that hippocampal ischemic neuronal damage almost eliminates all histological findings.…”
Section: Discussionmentioning
confidence: 99%
“…17 The dose range of topiramate reported in previous experimental studies is broad and often depends on the method of administration. For example, the efficacy of topiramate at a dose of 40-160 mg/kg/day in an inflammatory hyperalgesia model in rats 18 was demonstrated, and at a dose of 40 mg/kg/day 19 in studies on behavioral symptoms in rats. It has also been reported that hippocampal ischemic neuronal damage almost eliminates all histological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Systemically administration of topiramate has been previously tested in alcohol withdrawal in experimental animals and has been shown to suppress withdrawal symptoms 23 . Topiramate treatment also exhibits anxiolytic effect in both early and late periods of alcohol withdrawal 39 . Few studies have examined the effects of topiramate on morphine withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Topiramate reduced the anxiety and hyperactivity that developed in the course of alcohol withdrawal syndrome both in the earlier and later abstinence periods. Furthermore, there was no observed development of tolerance to the anxiolytic activity of topiramate [49].…”
Section: Przegląd Badań Przedklinicznychmentioning
confidence: 94%
“…Wykazano skuteczność topiramatu w zmniejszaniu niepokoju i nadpobudliwości w przebiegu alkoholowego zespołu abstynencyjnego -zarówno we wczesnym, jak i późniejszym okresie abstynencji. Co istotne, nie zaobserwowano rozwoju tolerancji na anksjolityczne działanie topiramatu [49].…”
Section: Review Of Clinical Trialsunclassified